Written grammatical errors committed by English language, non-native first entering students at the University of Limpopo : an exploration - Nkgadima, Godfrey Mapase (My University, 2022)
This study explores written grammar errors committed by UL first entering non-native English language students. The problem is that the standard of English among nonnative English language students does not seem to improve due to the recurrence of errors, and this has always occupied the attention of many L2 researchers. First year English language lecturers participated in the study; they were interviewed by the researcher to better understand issues related to errors committed by the students. The study is underpinned by Error Analysis theory. Content Analysis (CA) was employed to analyse the qualitative data obtained from the 30 students’ assignment scripts to obtain grammatical errors in the following: word classes, sentences, tense, punctuation, and paragraphing. The findings indicate that English non-native students committed errors in punctuation, sentence structure, noun, pronoun, subject-verb agreement– determiner–, spelling-, logical connectors-, contraction-, preposition-, incomplete sentence and wrong topic sentences errors. It recommends that the Department of Languages should introduce an annual English language competency test at the beginning of each year to access students’ English competency level. This will allow the ELLs to revise and develop teaching materials according to the language needs of the first-year students in the university
Thesis (M.A. (English Studies)) -- University of Limpopo, 2022
Keywords: English language; Students; First year; Grammatical errors; University of Limpopo; English language -- Grammar; College students; College freshmen